Features of sorbilact-L-arginine-combined action on the kidneys’ volumoregulatory function of patients with purulent-septic complications - Maksymchuk, N. O.; Konovchuk, V. M. (Journal of Education, Health and Sport, 2018)
The purpose of the work is to investigate the effect of combined use of sorbilact and L-arginine on the kidneys’ volume-regulatory function of patients with endogenous intoxication syndrome (EIS) of purulent-septic origin in the period of stabilization of secondary toxic autoagression. Methods. Indicators of kidney volume receptor function have been studied in patients of the following groups. The first group (І, control) consisted of 31 patients with systemic inflammatory response syndrome (SIRS). The second group (ІІ) consisted of 22 patients with EIS who were treated according to Surviving Sepsis Campaign 2016 (standard therapy) [9]. The third group (ІІ) consisited of 24 patients with EIS, who received sorbilact in addition to standard therapy. The fourth group (IV) included 21 patients with SEI who received standard therapy as well as Sorbilact and L-arginine. Sorbilact infusion to patients of III and IV groups was performed at a rate of 6-7 ml/kg body weight, intravenously dripping at a rate of 7-8 ml/min. After the end of infusion of sorbilact, patients of IV group were infused with 4.2% solution of L-arginine (“Tivortin” intravenous drip according to the instructions). Data was obtained and results gathered on the application of drugs in the period of stabilization of secondary toxic autoagresion (fourth day of drugs’ application). Findings. In the period of stabilization there is a restoration of the volume-regulatory function of the kidneys under standard therapy of endotoxicosis of purulent-septic genesis. The use of sorbilact with standard therapy activates the volume-regulatory function of the kidneys (in terms of sodium clearance by 31%, p <0,05) in the period of stabilization of toxic autoaggression. The combination of sorbilact with L-arginine increases the activity of sodium clearance by 12% (p <0,05) induced by sorbilact. Conclusions. The investigated features of basic adjuvant therapy with L-arginine and sorbilact can be recommended for use in order to restore the volume-regulatory function of the kidneys in cases of endotoxicosis of purulent-septic genesis.